Migrants, Refugees and Asylum Seekers' Integration in European Labour Markets A Comparative Approach on Legal Barriers and Enablers - Federico, Veronica; Baglioni, Simone (IMISCOE Research Series, 2021)
This open access book discusses how, and to what extent, the legal and institutional regimes and the socio-cultural environments of a range of European countries (the Czech Republic, Denmark, Finland Greece, Italy, Switzerland and the UK), in the framework of EU laws and policies, have a beneficial or negative impact on the effective capacity of these countries to integrate migrants, refugees and asylum seekers into their labour markets. The analysis builds on the understanding of socio-cultural, institutional and legal factors as "barriers" or "enablers"; elements that may facilitate or obstruct the integration processes. The book examines the two dimensions of integration being access to the labour market (which, translated into a rights language means the right to work) with its corollaries (recognition of qualifications, vocational training, etc.), and non-discriminatory working conditions (which, translated into a rights language means right to both formal and substantial equality) and its corollaries of benefits and duties deriving from joining the labour market. It thereby offers a novel approach to labour market integration and migration/asylum issues given its focus on legal aspects, which includes most recent policy changes and legal decisions (including litigation cases). The robust, evidence-based and comparative research illustrated in the book provides academics and students, but also practitioners and policy makers, with updated knowledge that will likely impact positively on policy changes needed to better address integration conundrums.